Selective inhibition of monoamine oxidase A by purpurin, an anthraquinone. Issue 5 (1st March 2017) - Lee, Hyun Woo; Ryu, Hyung Won; Kang, Myung-Gyun; Park, Daeui; Oh, Sei-Ryang; Kim, Hoon
Graphical abstract: Highlights: Purpurin was a potent and selective inhibitor for human MAO-A. IC50 value of purpurin belongs to the lowest group for natural products. Purpurin was a reversible and competitive inhibitor (Ki  = 0.422 μM). The binding affinity of purpurin for MAO-A was higher than that for MAO-B. Purpurin can be considered a new potential lead compound for development of novel RIMAs. Abstract: Monoamine oxidase (MAO) catalyzes the oxidation of monoamines that act as neurotransmitters. During a target-based screening of natural products using two isoforms of recombinant human MAO-A and MAO-B, purpurin (an anthraquinone derivative) was found to potently and selectively inhibit MAO-A, with an IC50 value of 2.50 μM, and not to inhibit MAO-B. Alizarin (also an anthraquinone) inhibited MAO-A less potently with an IC50 value of 30.1 μM. Furthermore, purpurin was a reversible and competitive inhibitor of MAO-A with a Ki value of 0.422 μM. A comparison of their chemical structures suggested the 4-hydroxy group of purpurin might play an important role in its inhibition of MAO-A. Molecular docking simulation showed that the binding affinity of purpurin for MAO-A (−40.0 kcal/mol) was higher than its affinity for MAO-B (−33.9 kcal/mol), and that Ile 207 and Gly 443 of MAO-A were key residues for hydrogen bonding with purpurin. The findings of this study suggest purpurin is a potent, selective, reversible inhibitor of MAO-A, and that it be considered a new potential lead compound for development of novel reversible inhibitors of MAO-A (RIMAs).